(untitled) (Revista Contexto & Educação, 2025)
This article aims to discuss Inclusive Education and teacher training in the Brazilian context, in the city of Vitória, in the State of Espírito Santo and in France, in the city of Bordeaux, in the Nouvelle Aquitaine region. The analysis is based on a qualitative approach based on focus groups, questionnaires and interviews, carried out in each context and based on a transnational reading, which allows us to reveal and understand how each of these countries, signatories of school inclusion policies, invest in the training of educators from an inclusive education perspective.The results of this research show that, in both countries, although there are policies aimed at different social groups, the understanding of Inclusive Education remains linked to the existence of Special Education, which can constitute a brake on the development of school inclusion and training of teachers within a broader perspective of the teaching and learning process.